A Case Study on Gob-Side Entry Retaining Technology in the Deep Coal Mine of Xinjulong, China. (29th September 2020) - Wang, Ping; Ding, Li; Ma, Yuan-jun; Feng, Tao; Sun, Guang-jing; Zhu, Yong-jian; Ren, Heng; Li, Peng; Zhang, Yu-qun; Wang, Xi-Zhi
Abstract : Through the analysis of the project of gob-side entry retaining in the deep gangue filling 2305S-2# working face of the Xinjulong coal mine, the principle and technology of surrounding rock control of gob-side entry retaining along the deep mining face are discussed. It is found that the use of gangue to fill the goaf of the deep mining face can effectively alleviate the occurrence of violent strata pressure, which is the basis for realizing entry retaining along the goaf. In the Xinjulong coal mine, the gangue wall and concrete-filled steel tube columns are used as roadside support structure. Anchor bolt + W steel belt are used as advance support, monomer column + hinged beam are used as temporary support, and long anchor cable + beam are used as permanent support. Gob-side entry retaining of deep mining working face is successfully realized. The actual measurement results show that the bearing capacity of gangue wall increases slowly, and the deformation is large. The concrete-filled steel tube column has a certain drilling bottom, and the roof cable is easily broken on the side of the remaining roadway. It is necessary to strengthen the lateral constraint of the gangue wall, limit the deformation of the gangue wall, and improve the bearing capacity of the gangue wall. The bottom of the concrete-filled steel tube column needs to be installed with a large backing plate to control the bottom drilling amount, and the roof anchor cable of the roadway must have a certain elongation to realize the coordinated deformation of the anchor cable and the roof.